(untitled) (Voice of History, 2023)
The political scientists have different opinion on the definition of democracy. Some defines democracy as the fall of an authoritarian government and conducting the first democratic elections. Other argues it as liberal reforms of an authoritarian regimes or structural adjustments made in authoritarian regimes or democratic reforms caused by the oppositional parties. In Nepalese context definition of democracy and democratic movement varies to other scholars. In Nepal it was started in against the totalitarian state of one family rule. The history of the Nepali democratic movement and its development is relatively new in the global context. The democratic movement in Nepal, seen as a conflict between the autocratic family and normal public those seeking their independence. As a result, the democratic movement in Nepal began as an anti-Rana movement. Prithvi Narayan Shah was fully aware of the value of public support for constructing a country. He launched the unification campaign with the help of the general public. When his successors abandoned the policy of Prithivi Narayan Shah- peoples participation in the politics, plots and violence entered in Nepali politics. As a result, Jung Bahadur came to the power and established the Rana rule in 1846. The political system, which is based on people’s participation for fundamental peoples right started to over throw an authoritarian and oppressive rule. The people were forced to launch a democratic movement in order to defend their rights in the country. Many Nepali heroes had sacrificed their life to established democracy in Nepal. The then state policy of marginalizing common people and absence of subaltern history writing practice, contribution of common people was not mentioned in the history book, especially, the contribution of the ethnic people. This article intends to identify the unidentified contribution of the ethnic freedom fighters – the Gurungs in the democratic movement of Nepal. It is a qualitative study focus on the historical events evaluating the contribution of the Gurung freedom fighters. In-depth interviews and library research method has been applied to gather data on the subject under discussion. It is limited to historical study on the subject. An attempt has been made to include the participation of Gurungs in the democratic movement of the period 1950- 1990. Generalization of the finding of this study can be applicable in the greater context.